Healing of bronchopleural fistula using a modified Dumon stent: a case report - Ferraroli, Giorgio Maria (BioMed Central, 2006)
BACKGROUND: Brochopleural fistula following lung resection is a therapeuric challenge for thoracic surgeons. CASE PRESENTATION: We describe a case of late bronchopleural fistula after right extrapleural pneumonectomy for malignant mesothelioma. Bronchoscopic attempts to repair it were unsuccessful. CONCLUSION: The use of a modified Y Dumon stent associated with glue apposition on the bronchial stump allowed us to close the fistula without the need of any surgical repair.